Efficacy and safety of Chinese herbal medicine for multiple sclerosis: a systematic review and meta-analysis of randomized controlled trials - Guan, Xiaorui; Wu, Yufan; Jia, Qiuyang; Zheng, Yilan; Zou, Mingrun; Liu, Jia; Sugimoto, Kazuo; Gao, Ying (Frontiers in Pharmacology, 2025)
BackgroundMultiple sclerosis (MS) is an incurable, chronic, disabling disease that primarily affects young adults. Chinese herbal medicine (CHM) is increasingly recognized as a major form of complementary and alternative medicine; however, there is a limited number of systematic analyses regarding its therapeutic effects on MS.Aim of the studyThis study aimed to evaluate whether CHM, when used alongside conventional treatment, offers additional therapeutic benefits for patients with MS, focusing on clinical efficacy and safety.Materials and methodsWe searched eight databases from their inception until July 2025 to identify eligible randomized controlled trials (RCTs) involving CHM therapy for MS. Key outcomes assessed included the expanded disability status scale (EDSS), annual relapse rate (ARR), neurological signs scores, clinical symptoms scores, and modified fatigue impact scale (MFIS). The risk of bias was evaluated using the Cochrane Handbook for systematic reviews, while quantitative synthesis was performed with RevMan (version 5.4.1) and Stata (version 18.0) software. This review has been registered at the International Prospective Register of Systematic Reviews database (Registration No. CRD42024605890).ResultsThis systematic review and meta-analysis included 28 RCTs involving a total of 1,971 participants. The combination of CHM and conventional therapy was superior to conventional therapy alone for individuals with MS. This was evidenced by a decrease in the EDSS (mean difference (MD) = −0.65; 95% confidence interval (CI): −0.96, −0.35; P < 0.0001; MD = −0.65, ARR (relative risk (RR) = 0.48; 95% CI: 0.31, 0.73; P = 0.0007), neurological signs scores (MD = −2.96; 95% CI: −4.52, −1.39; P = 0.0002), and MFIS (MD = −8.55; 95% CI: −10.20, −6.89; P < 0.00001). Additionally, there was an improvement in clinical effects (RR = 1.25; 95% CI: 1.19, 1.32; P < 0.00001). No serious adverse effect was reported.ConclusionAlthough the methodological quality of the included RCTs was relatively suboptimal, CHM therapy combined with conventional therapy manifests a promising effectiveness and safety for managing MS. Therefore, well-designed clinical studies are necessary to provide high-quality evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024605890, identifer CRD42024605890.